2008
DOI: 10.1007/s00432-008-0361-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Bmi-1 oncoprotein expression in NSCLC patients: a tissue microarray study

Abstract: Our results suggest that Bmi-1 is significantly associated with progression of NSCLC and might serve as a prognostic marker of adverse disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 38 publications
5
72
2
Order By: Relevance
“…11,12 In previous NSCLC studies, Vonlanthen et al 18 reported no association of Bmi1 expression with tumor characteristics (proliferation rate, differentiation, and size) or prognosis, whereas Vrzalikova et al 20 reported that Bmi1 expression was correlated with advanced stage and poor disease-free survival, but not with overall survival. For other types of cancer, some studies demonstrated that overexpression of Bmi1 was correlated with a poor prognosis [42][43][44] ; however, others reported that loss of Bmi1 expression was correlated with an aggressive phenotype, indicating a protective role of the Bmi1 protein.…”
Section: Bmi1 and Ezh2 Expression In Nsclc/kikuchi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In previous NSCLC studies, Vonlanthen et al 18 reported no association of Bmi1 expression with tumor characteristics (proliferation rate, differentiation, and size) or prognosis, whereas Vrzalikova et al 20 reported that Bmi1 expression was correlated with advanced stage and poor disease-free survival, but not with overall survival. For other types of cancer, some studies demonstrated that overexpression of Bmi1 was correlated with a poor prognosis [42][43][44] ; however, others reported that loss of Bmi1 expression was correlated with an aggressive phenotype, indicating a protective role of the Bmi1 protein.…”
Section: Bmi1 and Ezh2 Expression In Nsclc/kikuchi Et Almentioning
confidence: 99%
“…16,17 In previous studies on NSCLC, normal bronchial epithelial cells had abundant Bmi1 expression, whereas tumor cells had various expression patterns. 18,19 Vrzalikova et al reported that high Bmi1 expression was correlated with advanced stage and with poor disease-free survival in patients with early stage NSCLC who had received adjuvant chemotherapy, 20 whereas another group reported no association between Bmi1 expression and tumor characteristics (proliferation rate, differentiation, size, histology) or prognosis. 18 Thus, the clinical and clinicopathologic value of Bmi1 in NSCLC remains controversial.…”
mentioning
confidence: 99%
“…7 Katerina et al indicated that Bmi-1 was significantly associated with progression of NSCLC from a tissue microarray study. 8 Hu et al showed that the combination of USP22, PTEN, Bmi-1 and p-AKT markers was the independent prognostic indicator of overall survival in non-small-cell lung cancer. 9 The findings display that Bmi-1 is a significant prognostic factor of poor overall survival in lung adenocarcinoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…2). In particular, Bmi1 overexpression is correlated with poor prognosis for lung cancer patients (3). Bmi1 is an epigenetic chromatin modifier that acts as a key component of the PRC1 complex to mediate transcriptional repression.…”
mentioning
confidence: 99%